IS IT AS SIMPLE AS SAYING ‘EDUCATIONAL MANAGEMENT AND LEADERSHIP CHALLENGES?’ WHEN THE WALLS ARE SHAKEN, COCKROACHES WILL FALL: HEAD -ON -COLLISION WITH REAL CHALLENGES FACING UNIVERSITY LEADERS IN AFRICA: REALITY CHECK IN BOTSWANA - Majaha, Dr Ndlovu (The journal of contemporary issues in business and government, 2022)
Universities education Management is in the throes of a major transformation. This calls for a dedicated-entrepreneurial leadership crew set to release ‘the leadership nuclear’ amour at appropriate times to avert failures that could possibly be prevented. Decreasing public confidence, increasing concerns about higher education from state legislators, growing regulation at the state and national levels, fiscal challenges, globalization and other major concerns are facing African universities and higher education generally. This paper describes key principal and dynamic challenges confronting university leadership today, and provides a leadership operational framework that debunks these challenges. The paper is further premised on the fact that the university sector in Africa is experiencing unprecedented challenges affecting effective execution of their mandate. What is valuable about this study is enshrined in the study’s two leaf portal namely-providing a quality but comprehensive summary description of the prevailing common and unique challenges faced by Universities in Africa. Secondly the study provides a dossier to tackle selected leadership models that address these challenges in order to positively advance university education to the appropriate levels into the 21st century and beyond. Third and last, the study provides a platform for debate in dealing with contemporary challenges faced by current leadership within universities in Africa. I argue that the findings of this paper, contribute to the existing imbalances of information that characterize the current research in higher education. This contribution is particularly significant given the ongoing expansion of higher education throughout the world. The results of this study can be a foundation for futuristic research and assessment: for areas that require assessment in most African countries - aid in achieving a greater level of unification throughout most universities by amalgamating education policies and the adoption of policies and strategic planning to deal with various challenges alluded to throughout the study. Who knows; the glimmer of hope comes amid growing pressures on higher education leaders from within their universities and diverse outside forces, uncertain economic conditions, and the rapidly growing influence of technological innovations.The present study will provide a definitive direction and position in tenns of the challenges under investigation. The study further helps leaders in Universities to reflect on their own qualities as academic leadership and such reflection may help improve their leadership styles to achieve positive outcome and effective management of existing challenges.